A systematic literature review of project-based learning: research trends, methods, elements, and frameworks - Yusri, Radhya; Yusof, Anuar Mohd; Sharina, Azlin (International Journal of Evaluation and Research in Education (IJERE), 2024)
Project-based learning (PjBL) has been considered an effective learning model to improve the quality of learning in today’s world of education. This study aims to identify research trends of PjBL, research methods, elements or essential skills that can be improved, and a framework for implementing PjBL from 2016 to 2023. This review procedure includes searching, screening, evaluating, and synthesizing publications on PjBL. There were 34 articles published in Scopus-indexed popular journal. The research shows that the trends of PjBL from 2016 to 2023 have been conducted by using qualitative research for 26.47%, quantitative research for 35.29%, mixed methods for 8.82%, action research for 5.88%, descriptive research for 17.65%, and development research for 5.88%. The main elements that could be developed for students from PjBL are creativity, collaboration, critical thinking, communication, concept understanding, innovative thinking, motivation, problem-solving, and self-confidence. In this study, there are five frameworks studied. By criticizing those frameworks, a new framework is proposed called project-based learning and simulation (PjBLS).